2013
DOI: 10.56431/p-g7aa90
|View full text |Cite
|
Sign up to set email alerts
|

Minerals Content, Essential Oils Composition and Physicochemical Properties of <i>Citrus jambhiri</i> Lush. (Rough Lemon) from the Sudan

Abstract: Minerals content of Citrus jambhiri (rough lemon) fruit was qualitatively and quantitatively analyzed using atomic absorption spectroscopy (AAS) and flame atomic emission spectrometry (FAES). The peel, moisture and ash contents of rough lemon were found to be 18.35%, 23.75% and 2.04% respectively. Vitamin C (ascorbic acid) of rough lemon juice was found to be 70.0 mg/100 g. The chemical composition of essential oil of rough lemon peel was determined. The major compound was found to be limonene (84.5%) followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…2B), confirmed that S. aromaticum is a valuable source of potassium, calcium and iron. Potassium is important as a diuretic, calcium is important for muscles, teeth, bones and the heart (Brody, 1994) and iron is important for the formation of hemoglobin, oxygen and electron transfer in the human body, oxidation of fats, proteins, and carbohydrates, also, the function of the central nervous system, and (Mohammed et al, 2013). GC-MS confirmed presence of eugenol with percentages of (80.72% as listed in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…2B), confirmed that S. aromaticum is a valuable source of potassium, calcium and iron. Potassium is important as a diuretic, calcium is important for muscles, teeth, bones and the heart (Brody, 1994) and iron is important for the formation of hemoglobin, oxygen and electron transfer in the human body, oxidation of fats, proteins, and carbohydrates, also, the function of the central nervous system, and (Mohammed et al, 2013). GC-MS confirmed presence of eugenol with percentages of (80.72% as listed in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the species was found to have a rich source of minerals, e.g., Mg (0.20–021%), Ca (0.14–0.16%), K (0.72–0.82%), and Zn (0.12–0.24 mg/Kg). Mg is required in plasma and extracellular fluid to sustain osmotic balance ( 62 ). The findings reveal that wild vegetables include significant levels of Ca, K, and Zn, which are necessary nutrients for living organisms and are needed for the synthesis of chlorophyll and cell walls, as well as the transport of oxygen and electrons ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…El limoneno (84,5 %) se identificó en la cáscara del fruto de C. Jambhiri como componente principal en el estudio realizado por Abdelhafeez et al ( 2013) 24 , mientras que en el estudio de Ogunjinmi et al, (2019) 19 , el limoneno (4,64 %) se observó como un componente moderado en la cáscara del fruto de C. jambhiri de Nigeria.…”
Section: Composición Química Del Aceite Esencialunclassified